The discrete nature of grain attachment models in simulations of equiaxed solidification - Plotkowski, A.; Krane, M.J.M. (Applied mathematical modelling, 2017)
•Previous work reported channel segregates in simulations of equiaxed solidification.•This work investigates the underlying mechanism for their formation.•Two grain attachment models were considered.•The mechanism was found to be the assumption of discrete grain attachment events.•This conclusion suggests these defects are primarily numerical artifacts. Grain refiner is often added to aluminum and magnesium alloys during solidification processing to encourage the development of a fine equiaxed grain structure. Numerical modeling of such processes face the challenge of considering the effect of free floating grains that nucleate on grain refiner particles, are advected in the bulk fluid flow, and eventually coalesce to form a permeable, rigid solid structure. While several models have been developed to consider the advection of solid grains, the attachment of these grains is uniformly treated on a discrete, cell-by-cell basis. In a previous study, channel segregates were observed in the predicted composition field of equiaxed solidification simulations and were found to exhibit an extreme grid dependence. These channels were examined in the present study in detail for two different grain attachment models, one that assumed coalescence occurs at a constant and uniform volume fraction solid, and one that considered the effects of the local solid velocity field. The mechanism of the initiation and propagation of these channels was explored, and their physical relevance considered. It was concluded that these defects were primarily numerical artifacts arising from the discrete nature of the grain attachment models, and therefore, necessarily occurred on the length scale of the grid spacing. Development of an alternative attachment model that avoid this numerical problem is the subject of ongoing research.